Investigating Marl Formation and their Dominant Land use and Erosion in Kermanshah Province - Mosayeb Heshmati; Hamidreza Peyrovan; Mohammad Gheitury; Majid Ahmadi Molaverdi; Ali Moradpour (جغرافیا و پایداری محیط)
Land use/cover change at the geological marl formations, especially the conversion of forest and rangeland areas to rain-fed lands and subsequent improper tillage practice has led to severe soil erosion and sedimentation, soil moisture lost, dust-blown, global warming, and water pollution. The current study aims to prepare the spatial distribution of marl formation in Kermanshah province in Iran and to assess dominant land-use, plant cover, slope, and erosion features using satellite image (SPOT 2000) and field survey. The field data have been analyzed through ArcGIS software. The results of this study reveal that there are eight major marls formations in Kermanshah province including Amiran, Aghajari, Gachsaran, Gurpi, Talezangh, Kashkan, Pabdeh, and Mishan occupying about 24.21 % of province areas. Among these formations, three formations including Amiran, Kashkan, and Aghajari are the most vulnerable to degradation due to topographic conditions, high solubility, and improper land-use practices. The sensitive facies of Amiran and Kashkan Formations are more prominent in the forest and rain-fed areas with hill slope conditions. In these areas, deforestation, illegal charcoal extraction, improper agricultural and non-agricultural activities resulted in the dissolution of sensitive layered and consequently landslide incidents. Thus during each effective rainfall occurrence, there is severe erosion and siltation deliver fresh sediment in lower drainage systems affecting road, brigs, and farmlands. In gentle slope, this process causes head-cut and gully development. Aghajari formation, which covers a wide range of winter pastures in Kermanshah province, has a high potential of dissolution due to its mineralogical and soil properties increasing soil erosion and sediment yield. It is concluded that severe land use/cover change at marl formation of Zagros areas are the factors sensitive to soil erosion, sedimentation and flood hazard as well as the solution of serous crises such water deficiency and desertification. Extended Abstract 1-Introduction Geological Marl formations and their deposits are more sensitive to degradation and soil erosion factors. The considerable areas of Zagros regions in Iran comprise marl formations dominated by forest and rangeland land uses. These marls are different condition of topography and land use/cover, while they are characterized by high level of clay and slit contents and dominant swell-shrink clay minerals. Thus, the soils originated from these marl formations are vulnerable to plant cover degradation causing severe erosion, sediment and flood hazards. Landus in marly areas are forest and rangeland, hence; converting them to rain-fed areas and subsequently improper human practices such as heavy tillage and civil activities cause gully erosion and other soil erosion features, landslide occurrences, soil moisture lost and organic carbon emission. However, survey on marl formations in terms of land use/cove and dominant soil erosion at local scale are necessary steps to control environmental hazards, especially erosion, sediment, flood as well as drought, dust and water shortage managements in watersheds of west and east west of Iran. The present study aims to determinate the marl formation areas and to make a map for their distribution recognizing, some important local features like erosion in Kermanshah province (a part of upper Karkheh catchment) in Iran which were carried out during 2017-2020. 2-Materials and Methods This research conducted in Kermanshah province comprising verity of geological formations mainly marl deposits which are the hilly and plain topography. In other to achieve this research, the border of each marl formation was mapped using basal geological map and field verification. Next the dominant erosion feature was determined using satellite image (SPOT), but the land use was mapped through Landsat 8 (2015). Finally, field survey carried out for exploring details of land use and erosion features using GPS. The soil erosion features were inter-rill, rill, gully and landslide. Furthermore, land use was forest, rangeland and agricultural areas. The spatial distribution and area of main erosion feature and land use within each marl formation was mapped using ArcGIS. 3-Results and Discussion The findings reveal that there are eight major marl formations in Kermanshah province including Amiran, Aghajari, Gachsaran, Gurpi, Talezangh, Kashkan, Pabdeh, and Mishan occupying approximately 603 million ha (24.21 % of province areas).Among these formations, three formations of Amiran, Kashkan, and Aghajari are the most vulnerable to degradation due to higher area, topographic conditions, high solubility, and improper land-use practices. Field verification showed that solubility phenomenon in both Kaskan and Amiran formations is considerable where, forest and rangeland are degraded or rain-fed areas is subjected to up-down the slope tillage practice. They are more sensitive to land use change and field survey showed severe inter-rill, rill and landslide incidence where subjected to converting forest, tillage practice, charcoal extraction and improper civil activities. In some areas, that forest is wholly cleared, after each effective rainfall occurrence, fresh sediment from hill slope of Amiran and Kashkan damage the road, bridge, riverside and lowland agricultural areas. Moreover, in plane areas, dissolve phenomenon contributes to head-cut activity developing of gully erosion. For instance, in Bujan area (SW Kermanshah city), sever tunneling erosion and landslide are delivered the fresh sediment comprising greenish clay and slits fractions during rainfall. This sediment moves down through runoff in parallel to slope furrow of tillage at the rain-fed lands. Consequently, this sediment contaminates surface water, accelerates local flood hazard and covers farmlands in lower parts. It can be said that the deforestation rate is less visible in this province. Therefore, as one of the upstream branches of Karkheh basin, it has a key origin of flood occurrence and sediment yield and its accelerating damages in Lorestan (Pol-e Dokhtar) and Khuzestan provinces. This destruction continues in an astonishing way, away from improper management and monitoring. Aghajari formation, which covers a wide range of winter pastures in Ghasr-e-shirin, has a high potential of dissolution phenomenon due to its mineralogical and soil properties increasing soil erosion and sediment yield. It is more vulnerable, where subjected to land use change, particularly converting rangeland to irrigation lands. 4-Conclusion According to findings, most of the marl formations in Kermanshah province have more outcrops in the upper and middle parts of watersheds and continue in Lorestan, Ilam and Khuzestan provinces which induces same conditions for environmental hazards such as floods, soil erosion and dust phenomena. The reason for the destruction of these marl formations is the change in land use, especially the conversion of forests and rangeland to rain-fed areas causing various forms of erosion, including dissolution, rill, gully and landslides. Field studies reveal that most facies of these marl formations contain clay, silt and shale with thin to medium sandstone layers. Due to mineralogical property and high amounts of clay and silt fractions as well as topographic factors, they are prone to dissolution, erosion and landslides hazard, which are increased by land use change in forest and rangeland areas, vegetation destruction and improper tillage practice. In this condition, fine-grained sediments reach the drainage system during rainfall time. The consequencs of this process, in addition to sediment, are the flood hazard, water shortages impacting proper management of such crises in the Zagros regions. In Qasr-e-shirin areas, extensive land use change at Aghajari formation not only causes soil erosion, sediment and flood problems, but also potentially is the dust blown origin due to the prevailing wind direction (from east to west), that can affect Kermanshah, Lorestan, Hemedan and Markazi province of Iran.